Acetyl-11-keto-beta-boswellic acid (AKBA): structure requirements for binding and 5-lipoxygenase inhibitory activity. - Sailer, E. R. (1996)
1. 5-Lipoxygenase (5-LOX) products from endogenous arachidonic acid in ionophore-stimulated peritoneal polymorphonuclear leukocytes (PMNL) and from exogenous substrate (20 microM) in 105,000 g supernatants were measured. 2. The effects of natural pentacyclic triterpenes and their derivatives on 5-LOX activity were compared with the inhibitory action of acetyl-11-keto-beta-boswellic acid (AKBA), which has been previously shown to inhibit the 5-LOX by a selective, enzyme-directed, non-redox and non-competitive mechanism. 3. The 5-LOX inhibitory potency of AKBA was only slightly diminished by deacetylation of the acetoxy group or reduction of the carboxyl function to alcohol in intact cells (IC50 = 1.5 vs. 3 and 4.5 microM, respectively) and in the cell-free system (8 vs. 20 and 45 microM). 4. beta-Boswellic acid (beta-BA), lacking the 11-keto function, inhibited 5-LOX only partially and incompletely, whereas the corresponding alcohol from beta-BA, as well as amyrin, acetyl-11-keto-amyrin, 11-keto-beta-boswellic acid methyl ester had no 5-LOX inhibitory activity up to 50 microM in either system. 5. beta-BA only partially prevented the AKBA-induced 5-LOX inhibition, whereas the non-inhibitory compounds, amyrin and acetyl-11-keto-amyrin, almost totally antagonized the AKBA effect and shifted the concentration-inhibition curve for the incomplete inhibitor beta-BA to the right. In contrast, the non-inhibitory 11-keto-beta-BA methyl ester exerted no antagonizing effect. 6. The results demonstrate that the pentacyclic triterpene ring system is crucial for binding to the highly selective effector site, whereas functional groups (especially the 11-keto function in addition to a hydrophilic group on C4 of ring A) are essential for 5-LOX inhibitory activity.